Mechanisms and Conditions for the Substitution of the Plant Tissue in Petrified Wood with Silicious Minerals - Khamadiev R.I.; Khassanov R.R. (Учёные записки Казанского университета: Серия Естественные науки)
The fragments of petrified wood from the Permian deposits at the territory of Tatarstan were studied. Petrified wood is characterized by silification of the plant tissue with retention of its primary texture. Wood samples were investigated using optical microscopy, carbon isotope analysis, and electron microscopy with microprobe analysis. The mechanisms of substitution of the wood organic matter with soluble and colloidal silica were specified. Details were provided on paleoclimatic conditions for the growth of higher plants during the period of Permian sedimentation.